(untitled) (Journal of Forensic Medicine & Toxicology, 2022)
Estimation of stature is one of the three main parameters used for establishing the identity of unknown cadavers, others being age and sex. This becomes more important when forensic expert is presented with highly decomposed, mutilated and dismembered bodies. Present descriptive observational study was conducted to estimate stature from lengths of different parts of the sternum by deriving linear regression equations. We used 52 fresh sterna obtained from male cadavers of age more than 25 years brought for medicolegal autopsy in this tertiary care centre located in Vindhya region of Madhya Pradesh. Correlation between stature and length of manubrium, mesosternum and combined length of manubrium and mesosternum studied and simple linear regression equations were derived. We observed a moderately positive correlation between stature and length of mesosternum (R=0.415) and combined length of manubrium and mesosternum (R=0.451). Combined length of manubrium and mesosternum (CL) has the highest accuracy for estimating stature of all the other parameters considered in the present study [standard error of estimate (SEE)- 5.56]. Simple linear regression equation derived was Stature=121.2 + 0.272 x CL. Regression equations derived in the present study are useful when rapid estimation of stature is required for guiding investigating authorities for establishing identity of cadavers and there is no time for maceration. However, when compared to other parameters like lengths of long bones, hand length and foot length, lengths of different parts of the sternum are less accurate in estimating stature.